2017
DOI: 10.1002/aic.15991
|View full text |Cite
|
Sign up to set email alerts
|

The lift on a disc immersed in a rotating granular bed

Abstract: The discrete element method has been used to study the lift F L on a stationary disc immersed coaxially in a slowly rotating cylinder containing a granular material. In a tall granular column, F L rises with the immersion depth h, but reaches a roughly constant asymptote at large h, in agreement with previous studies. Our results indicate that the argument in some earlier studies that F L is proportional to the static stress gradient is incorrect. Instead, our results show that the lift is caused by an asymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…There are six parameters in the model for the contact forces between particles: the spring constants and , the damping constants and , the coefficient of interparticle friction and the coefficient of particle–wall friction . Following Debnath, Rao & Nott (2017), we choose , , , and , where and are the density and the diameter of the particle, respectively, and is the acceleration due to gravity. It is widely acknowledged that should be a few orders of magnitude larger for materials such as aluminium, stainless steel, brass and glass beads (see e.g.…”
Section: Details Of the Demmentioning
confidence: 99%
See 1 more Smart Citation
“…There are six parameters in the model for the contact forces between particles: the spring constants and , the damping constants and , the coefficient of interparticle friction and the coefficient of particle–wall friction . Following Debnath, Rao & Nott (2017), we choose , , , and , where and are the density and the diameter of the particle, respectively, and is the acceleration due to gravity. It is widely acknowledged that should be a few orders of magnitude larger for materials such as aluminium, stainless steel, brass and glass beads (see e.g.…”
Section: Details Of the Demmentioning
confidence: 99%
“…The time step used is 1.2 × 10 −4 d p /g. Debnath et al (2017) estimated the lift on a disc immersed in a rotating bed of granular material, and found that modest changes in the value of k n by a factor of 10 do not affect the normal stresses exerted on the disc significantly. The value of k t /k n is commonly used; it is obtained by considering an elastic collision between a sphere and a flat surface, assuming that the time periods for normal and tangential collisions are equal (Shäfer et al 1996).…”
Section: Details Of the Demmentioning
confidence: 99%
“…As the computational time step is proportional to , a large value of makes the simulations computationally expensive. Hence the value of is chosen in the range , and is set to (Debnath, Rao & Nott 2017). The damping coefficient is chosen so that normal coefficient of restitution for the interaction between two particles, , is set equal to .…”
mentioning
confidence: 99%